INTERPRETING SCIENTIFIC APPROACH IN NATURAL SCIENCE SUBJECT FOR ELEMENTARY SCHOOL: AN INTEGRATIVE STUDY - Saefudin, Asep; Saputri, Aprilia Eki (Unnes Science Education Journal, 2018)
This research employs conceptual analysis with integrative study (Whittemore & Knafl 2005), using five steps of identifying problems, literature study, evaluation of data, analysis of data, and reporting (Whittemore & Knafl, 2005). The result of this research concludes that the learning process of natural science concerning five essential steps. These five steps emphasize on the processes (competences) which should be done or reached by students, which are 1) observing things and or occasion, 2) asking about things and or occasion which are just observed on its relevance, 3) trying to (gather information) to answer the questions in the step of asking, 4) analyzing the obtained information or taking conclusion based on the analysis of data, and 5) communicating the result of experiences from the previous steps in written or oral regarding.